ANALISIS KELAYAKAN RENCANA PEMEKARAN WILAYAH (REGIONAL EXPANSION) DI KECAMATAN KOTO TANGAH KOTA PADANG - reshy novaria putri; Fitriana Syahar (DEPARTEMEN GEOGRAFI FIS UNP, 2020)
This study aims to analyze the regional splitting plan in Kecamatan Koto Tangah, Kota Padang by knowing what factors influence the regional expansion plan in Kecamatan Koto Tangah in terms of administrative, physical and regional requirements based on Peratutran Pemerintah No. 19 of 2008 Tentang Kecamatan. The research method used in this study is a quantitative descriptive method with a spatial approach. The sample area in this study is the Kecamatan Koto Tangah with all the existing villages. The analysis technique used in this research is the study of literacy, interviews and formulations used in reference to Peratutran Pemerintah No. 19 of 2008 Tentang Kecamatan. The feasibility analysis of the expansion plan of the Kecamatan Koto Tangah area was analyzed based on administrative, physical and regional requirements. The results of this study indicate that the administrative requirements are not yet feasible to be expanded, whereas physically the territorial area is feasible to be expanded and technically it is also feasible to be expanded.